Kedudukan Penyidik Pegawai Negeri Sipil Direktorat Jenderal Pajak dalam Kerangka Penegakan Hukum Pidana Perpajakan di Indonesia - Farrel Alanda Fitrah; Agus Takariawan; Zainal Muttaqin (CV. Social Politic Genius (SIGn), 2021)
This study aims to investigate the position of the DGT’s Civil Servant Investigator in relation to their duty to enforce taxation criminal. The law enforcement of taxation criminal in Indonesia is involving several institution like Civil Servant Investigator (Directorate General of Taxes Institution), Police Investigator (Indonesian Police Institution), and Attorney Investigator (Attorney Institution). This involving, which lately leads to the position and authority problem of each institution. This study will be focused on the position of civil servant investigator of Directorate General of Tax and its relation with other party like Supervisory Coordinator which occupied by police investigator, and also other investigator from another institution. The method which is used in this study is normative juridical approach with analytical descriptive specification. Based on that method, then the researcher will compare between the position of DGT’s Civil Servant Investigator ‘in legislation’ and ‘in its practice’ through library study and field research. The researcher carry out this research based on the researcher’s consideration about the importance of state income from the taxation sector, so that the unlawful act that detrimental from the taxpayer and any related party of it can be eradicated immediately. The results shows that the position of the DGT Civil Servant Investigator in the framework of eradicating taxation criminal was emphasized as the primary investigator. This position is based on Law No. 16 of 2009 as lex specialis derogat legi generalis against Law No. 8 of 1981. Based on this position, there some friction that occurs between the DGT Civil Servant Investigator and other officer from another institution. For example, the DGT Civil Servant Investigator of the West Sumatra-Jambi Regional Office, which was designated as a suspect by the Police investigator, and the Mobile 8 tax restitution was handled by the Attorney Investigator. One of the factors that causing the friction is the difference in organizational culture of each related institution. Therefore, the researcher recommend that each institution should understand carefully what their primary function is in dealing with taxation criminal so that there will be no misunderstanding and potency of overlapping between related institutions which can interfere the law enforcement process.